ANALISIS BENTUK PRODUK KERAMIK STUDIO MANDIRI DENGAN TEMA TRADISI LOKAL INDONESIA MELALUI PENDEKATAN ‘ATUMICS’ - Ardini, Sasanti Puri; Winata, Gita (LP2M ISBI Bandung, 2023)
Indonesia, known for its rich cultural diversity and traditional practices, offers a wide range of ceramic products that have a strong basis in tradition. These creations appear from the artistic endeavors of individual artists, independent studios, and craft-based industries. The scope of diversity extends beyond the topic of the field of tradition, which includes a combination of technical abilities and materials used for the creation of a piece, thus implementing a transformation of a local tradition into an innovative and creative product. This article present an exhibition and analysis of independent studio and craftbased industries ceramics products that explore the theme of local Indonesian traditions through the application of the The ATUMICS method is a way of Transformation Tradition that was introduced by Adhi Nugraha. The study using the ATUMICS framework, which refers Artifact (A), Technique (T), Utility (U), Material (M), Icon (I), Concepts (C) and Shape (S). These models were utilized to define the components that were found in ceramics products originating from three different ceramic studio or craft-based industries in Indonesia. The research results provide insight into which elements can be applied and combined through the ATUMICS method to enhance local traditions in ceramics. Keywords: ceramic, craft, product, tradition, atumics